HALAL TOURISM PROMOTION USING E-COMMERCE SOCIAL MEDIA ON TOURIST VISIT: â€œSTUDY IN BENGKULU PROVINCEâ€ - Eska Prima Monique Damarsiwi; Nia Indriasari; Ida Anggraini (JELAJAH: Journal of Tourism and Hospitality, 2020)
The concept of tourism today is divided into two, namely conventional tourism and halal tourism. Halal Tourism is a form of cultural-based tourism that promotes the values ​​and norms of Islamic Sharia as its basic foundation. In this digital age millennials access all information through cyberspace. So as to be able to spread information and capture market share in tourism we can utilize electronic marketing or e-marketing. E-marketing or electronic marketing refers to the application of marketing principles and techniques through electronic media and more specifically the internet. E-commerce is a sales system that developed after the discovery of the Internet. This marketing system can be felt to reach the entire world simultaneously without the need for representative branches in all countries. Besides marketing like this can be done 24 hours without stopping in marketing the products. Bengkulu Province Tourism Office data recorded the number of domestic and foreign tourist arrivals in 2018 of 662,766 visits, 798 visits came from foreign tourists (tourists). In 2019, it is targeted to increase the number of domestic tourist visits to reach 394,265–420,025 and tourists to reach 3,972–4,995 visits. With the target of increasing tourist arrivals in Bengkulu, the local government must be more vigorous in terms of tourism promotion in Bengkulu Province. Bengkulu Province which began to face the challenges of tourism was felt to be able to start introducing Halal Tourism as a new Brand in its tourism activities. The difference of this research with the previous one is the independent variable Halal Tourism (X1) by using dimensions: Halal Destination, Halal Public Facilities, Halal Lifestyle, Halal Food in Bengkulu Province. This study uses intervening variables E-Commerce Social Media (Y) which uses dimensions: Context, Communications, Collaboration, Connection to determine the effect on the dependent variable of tourist visits (Z) in Bengkulu Province. This research uses qualitative analysis.The type of data collected in this paper is primary data carried out by distributing questionnaires in the field to get a clear picture of the potential of Halal Tourism using E-Commerce Social Media to increase tourism visits in Bengkulu Province. . The number of samples taken was 150 respondents who met the criteria set by the researcher. The results of the study stated that Halal Tourism (X1) has a significant influence on the variable E-Commerce Social Media (Y). independent variable Halal Tourism (X1) and intervening E-Commerce Social Media (Y) have a significant and partial significant effect on the tourist visit variable (Z). By using the sobel test, the results are obtained that the intervening coefficient has a significant influence on the variable Halal Tourism (X1) on the variable Tourist Visits. Conclusions obtained by researchers that the Government of Bengkulu Province began to be able to introduce halal products in Bengkulu Province, improve existing facilities to make it more Islamic, introduce the Tabot festival which is a traditional warning greeting containing Islamic elements, build sharia hospitality , multiply information about halal food in Bengkulu Province. Such information can be disseminated on the Bengkulu government's tourism website, tourism agency social media accounts, travel agents in Bengkulu Province and outside Bengkulu Province in order to attract local and foreign tourists.